Development of a targeted client communication intervention for pregnant and post-partum women: a descriptive study. (July 2021) - Bogale, Binyam; Mørkrid, Kjersti; O'Donnell, Brian; Ghanem, Buthaina; Abu Ward, Itimad; Abu Khader, Khadija; Isbeih, Mervett; Frost, Michael; Baniode, Mohammad; Hijaz, Taghreed; Awwad, Tamara; Rabah, Yousef; et al.
Abstract: Background: Targeted client communication using text messages can inform, motivate, and remind pregnant and postpartum women to use care in a timely way. The mixed results of previous studies of the effectiveness of targeted client communication highlight the importance of theory-based co-design with users. We planned, developed, and tested a theory-based intervention tailored to pregnant and postpartum women, to be automatically distributed via an electronic maternal and child health registry in occupied Palestinian territory. Methods: We did 26 in-depth interviews with pregnant women and health-care providers in seven purposively selected public primary health-care clinics in the West Bank and Gaza to include clinics with different profiles. An interview guide was developed using the Health Belief Model to explore women's perceptions of high-risk conditions (anaemia, hypertension, diabetes, and fetal growth restriction) and timely attendance for antenatal care, as predefined by a national expert panel. We did thematic analyses of the interview data. Based on the results, we composed messages for a targeted client communication intervention, applying concepts from the Model of Actionable Feedback, social nudging, and enhanced active choice. We assessed the acceptability and understandability of the messages through unstructured interviews with local health promotion experts, health-care providers, and pregnant women. Findings: The recurring themes indicated that most women were aware of the health consequences of anaemia, hypertension, and diabetes, but that they seldom associated these conditions with pregnancy. We identified knowledge gaps and low awareness of susceptibility to and severity of these complications and the benefits of timely antenatal care. The actionable messages were iteratively improved with stakeholder and end-user feedback after presenting the initial draft, and the messages deemed were understandable and acceptable based on reflections during unstructured assessment. Interpretation: Following a stepwise iterative process by a theory-based approach and co-designing the intervention with users, we revealed elements critical to an efficacious targeted client communication intervention. A potential limitation of our study is that conducting in-depth interviews on several health conditions simultaneously might have reduced the depth of information we could have obtained. The strength of our study was that we assessed for, developed, and refined the intervention following recommended theoretical frameworks and best practices. The effectiveness of this intervention is under evaluation in a cluster-randomised trial (ISRCTN10520687). Funding: European Research Council and Research Council of Norway.